Steganography in Thermal Image using Fusion technique on Pattern Drawing and Knight’s Tour Algorithm - S.Rathika , Dr.R.Gayathri (International Journal of Advanced Science and Technology, 2020)
Steganography plays a vital role that ensures security to the information which has a threat to get hacked. The recent technology and development in the computer field, has articulated so many encryption algorithm and hacking algorithms as well, in the field of secret communication. Hence, the necessity of an updated protection mechanism is increasing day by day. Therefore, in this paper, we proposed a system with a Knight’s Tour Algorithm, where a pattern drawn on the count of a Knight’s Tour on the chessboard and picked the number from the nodes selected, while matched with thermal image, the color values of the selected nodes were converted to grey color on one hand and on the other hand, the stepwise movement of the Knight Tour is numbered and converted to a barcode image and fused with thermal image simultaneously to hide the existence of the secret data. Collectively, a multiple guaranteed security services is incorporated, formulated, and tested. The level of security provided to the system is made challenging by applying the Knight Tour algorithm, thereby increased the complexity to the intruder from breaking the secret.